Vietnam’s Exports in the Period of 2016-2023 and Main Solutions to Promote Exports to 2030 - Ngo, The Chi; Dao, Ngoc Ha (Business and Economic Research, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Export is considered one of the prime essential factors for the socio-economic development of a country. In recent years, Vietnam’s exports have achieved positive results. However, in the face of unpredictable developments in the world’s economic and political situation, Vietnam must continue promoting exports up to 2030. This article presents and analyzes an overview of the export situation in the 2016-2023 period and proposes some solutions to boost exports up to 2030.